Crambe affected by biological and chemical seed treatments - Junior Cattaneo, Alex; Stangarlin, Jose Renato; Bassegio, Doglas [UNESP]; Santos, Reginado Ferreira (Inst Agronomico, 2016)
Crambe has great potential for cultivation in tropical regions, but its biotic factors may be a limiting aspect for its production. Thus, we aimed in this study to assess the effect of pre-sowing seed treatments on seedling emergence, root system, production components, and oil. The experiment was conducted during two years in Cascavel, Parana, Brazil. The experimental design consisted of randomized blocks with six treatments, including a control treatment (no treatment), biological treatments (Trichoderma asperellum and Bacillus subtilis), and chemical treatments (glutamic acid, thiamethoxam and zinc), with four replications. Emergence and growth crambe, as well as production components and oil in the first year were higher due to the contrast in the agricultural years. In the first year, the chemical treatment with thiamethoxam stood out for emergency of plants. Seed treatments did not influence the growth of the aerial parts of the plants, but provided an increase in the root system, especially zinc. Biological (T. asperellum and B. subtilis) and chemical (thiamethoxam) seed treatments led to higher crambe yield when compared to the control treatment; however, the biological treatment with T. asperellum provided less oil.
Keywords: Bacillus subtilis; Trichoderma asperellum; thiamethoxam; glutamic acid; zinc